DISIPLIN KERJA APARATUR SIPIL NEGARA TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN SIDENRENG RAPPANG - Muliani Muliani (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract The purpose of this study is to find out the Work Discipline of the State Civil Apparatus Against the Quality of Public Services at the Sidenreng Rappang District Population and Civil Registry Office.The population in this study was 1.339 consisting of 35 civil servants in the office of the populasion and the district civil regestry and the people who served 1.304f for one month. The sampling technique uses the Slovin formula with 93.05 results rounded up to 93 respondents, taken based on Purposive Sampling techniques. This type of research is quantitative descriptive. Data collection techniques used in this study were observation, questionnaire, literature study and secondary data. The data analysis technique used is validity test, reliability test using SPSS 16.0 and Likert Scale. Based on the results of the research from if the questionnaire obtained recapitulation of the work discipline variables of the state civil apparatus (X), obtained an average percentage of 65% is included in the